Comparison of Safety and Efficacy of Intrauterine Foley’s Catheter Balloon and Uterovaginal Packing in Patients with Excessive Vaginal Bleeding after Vaginal Delivery - Andleeb Khalid, Bushra Khan, Shermeen Kousar, Humera Rizwan, Sumera Malik, Amina Jamil (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To compare the safety and efficacy of uterovaginal packing and Foley’s catheter balloon tamponade in patients with excessive vaginal bleeding following vaginal delivery. Design : RCT ( Randomized Controlled Trial). Setting : Obstetrics & Gynaecology Deptt. , HFH ( holy family hospital) , RWP. Duration: Six Months. Materials & Methodology: 94 females who presented with excessive vaginal bleeding ( > 500 ml) following vaginal delivery, 18 to 40 years of age , gestational age (GA) ≥37 weeks were included. Patients with retained products of conception, PPH due to perineal, cervical or vaginal tear and coagulation disorders were excluded. The patients were distributed equally into 2 groups ; a and b based on the lottery method. Group a was managed with uterine packing and Group b was managed by the Foley’s catheter balloon tamponade. Efficacy and safety in both groups was measured. Results: In my study, efficacy was significantly high in uterine packing group (Group a) compared to Foley’s catheter balloon tamponade (group b) (89.36% versus 68.09%; respectively) with p-value of 0.012. In my study, safety was significantly high in uterovaginal packing group (Group a) compared to Foley’s catheter balloon tamponade (group b) (72.34% versus 31.91%; respectively) with p-value of 0.0001. Conclusion: Uterovaginal packing is more secure, prompt and efficient procedure to manage excessive hemorrhage after delivery compared to Foley’s catheter balloon tamponade. Keywords: Hemorrhage, uterovaginal packing ,foley’s balloon tamponade.